Growth performance and blood profiles of striped catfish (Pangasianodon hypophthalmus) fed leaves extract of Myrmecodia tuberosa - RUDY AGUNG NUGROHO; ESTI HANDAYANI HARDI; YANTI PUSPITA SARI; RETNO ARYANI; RUDIANTO RUDIANTO (Nusantara Bioscience, 2019)
Abstract. Nugroho RA, Hardi EH, Sari YP, Aryani R, Rudianto. 2019. Growth performance and blood profiles of striped catfish (Pangasianodon hypophthalmus) fed leaves extract of Myrmecodia tuberosa. Nusantara Bioscience 11: 89-96. The application of plant extract in the aquaculture field is gaining momentum. This study aimed to determine the effects of M. tuberosa Jack leaves extract on the growth performance and blood profiles of striped catfish (Pangasianodon hypophthalmus). 400 fish with an initial average weight of 1.54 ± 0.02g were randomly divided into five groups and fed with different concentration of M. tuberosa Jack leaves extract (0.25, 0.5, 1, 2%) and control diet for 80 days. Growth performance, feed conversion rate, feed efficiency, survival rate, morphometric, and hematological profile of the fish were evaluated at the end of the trial. The results found that fish fed 0.5-1% concentration had significantly higher (P<0.05) growth, feed conversion rate, feed efficiency, morphometric value, survival, white blood cell, hemoglobin, neutrophil, lymphocyte, and monocyte than control. Meanwhile, supplementation of 2% MTE in the diet of fish reduced growth, feed utilization, viscerosomatic index, and morphometric values but increased red blood cell. All the supplemented diets decreased platelet of fish. The findings indicated that supplementation 0.5-1% of MTE is beneficial to the growth and blood profile of fish through the increment of growth indices, feed utilization, white blood cell, hemoglobin, neutrophil, lymphocyte, and survival rate of fish.